2019
DOI: 10.24875/ric.18002630
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease: Perspectives for Primary Health Care

Abstract: Background: Chronic obstructive pulmonary disease (COPD) has become a major health challenge worldwide due to its increasing incidence and mortality, which have serious repercussions for health-care systems. Methods: We conducted a review of international efforts to control COPD in primary care. Results: The WHO created the Alma-Ata declaration which established for the first time, access to health care as a human right. This precept led to the implementation of numerous programs including practical approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…We also found that the prevalences of studies conducted in primary care centers and hospitals were higher compared to those studies conducted in the community. This is possibly because primary care centers and hospitals care for symptomatic individuals and individuals with risk factors for the disease [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the prevalences of studies conducted in primary care centers and hospitals were higher compared to those studies conducted in the community. This is possibly because primary care centers and hospitals care for symptomatic individuals and individuals with risk factors for the disease [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The greatest risk factors for the development of emphysema are cigarette smoke but also other toxic gases as well as particulate matter and household air pollution [215][216][217][218]. The lack of the endogenous ability to regenerate and the almost complete absence of therapeutic measures to halt or reverse tissue damage make COPD an incurable disease whose progression can currently at best be slowed [219].…”
Section: Aox To Combat Smoke-induced Emphysema In the Mousementioning
confidence: 99%
“…Our hope is that it will be maintained and reinforced by the new government. INER developed a proposal for respiratory care with the characteristics of Practical Approach to Lung Diseases (PAL), including the most common diseases and a real possibility for improving primary care . Interestingly, we observed the surprising exponential growth of pharmacy‐associated outpatient clinics after the government introduced the requirement of a prescription to purchase antibiotics.…”
mentioning
confidence: 98%